Proceedings of the International Conference on Microelectronics, Computing & Communication Systems MCCS 2015 (Lecture Notes in Electrical Engineering,, 2018)
This volume comprises select papers from the International Conference on Microelectronics, Computing & Communication Systems(MCCS 2015). Electrical, Electronics, Computer, Communication and Information Technology and their applications in business, academic, industry and other allied areas. The main aim of this volume is to bring together content from international scientists, researchers, engineers from both academia and the industry. The contents of this volume will prove useful to researchers, professionals, and students alike.